Development of novel alginate based hydrogel films for wound healing applications - Pereira, Rúben (2019)
Alginate and Aloe vera are natural materials widely investigated and used in the biomedical field. In this research work, thin hydrogel films composed by alginate and Aloe vera gel in different proportions (95:5, 85:15 and 75:25, v/v) were prepared and characterized. The films were evaluated regarding the light transmission behavior, contact angle measurements, and chemical, thermal and mechanical properties. These thin hydrogel films, prepared by crosslinking reaction using 5% calcium chloride solution, were also investigated relatively to their water solubility and swelling behavior. Results showed that Aloe vera improved the transparency of the films, as well their thermal stability. The developed films present adequate mechanical properties for skin applications, while the solubility studies demonstrated the insolubility of the films after 24 h of immersion in distilled water. The water absorption and swelling behavior of these films were greatly improved by the increase in Aloe vera proportion.